The DCR protein TTC3 affects differentiation and Golgi compactness in neurons through specific actin-regulating pathways. - Gaia Elena Berto; Cristina Iobbi; Paola Camera; Elena Scarpa; Corinne Iampietro; Federico Bianchi; Federico Bianchi; Marta Gai; Francesco Sgrò; Flavio Cristofani; Annette Gärtner; Carlos G Dotti; et al. (PLoS ONE)
In neuronal cells, actin remodeling plays a well known role in neurite extension but is also deeply involved in the organization of intracellular structures, such as the Golgi apparatus. However, it is still not very clear which mechanisms may regulate actin dynamics at the different sites. In this report we show that high levels of the TTC3 protein, encoded by one of the genes of the Down Syndrome Critical Region (DCR), prevent neurite extension and disrupt Golgi compactness in differentiating primary neurons. These effects largely depend on the capability of TTC3 to promote actin polymerization through signaling pathways involving RhoA, ROCK, CIT-N and PIIa. However, the functional relationships between these molecules differ significantly if considering the TTC3 activity on neurite extension or on Golgi organization. Finally, our results reveal an unexpected stage-dependent requirement for F-actin in Golgi organization at different stages of neuronal differentiation.